Effectiveness of sulfur-coated and uncoated urea fertilizers as nitrogen sources for rice - Said, Nur Fazlina (2012)
The efficiency of urea N in rice culture is usually as low in Malaysian soil. The low N use efficiency is attributed mainly to ammonia volatilization, denitrification, leaching, and run off losses. Various methods have been developed in order to improve urea-N consumption by rice. The concurrent use of physical methods such as coating with sulfur, using urease inhibitor and the additive of soluble salts were used in order to increase the urea-N utilization in rice. The objective of this study is to determine the efficacy of sulfur coated urea (SCU) as N source for rice. The following are the specific objective to conduct in this study (i) To evaluate physical and chemical properties of the sulfur coated urea, ii) To quantify N transformation, ammonia volatilization and pH changes in soil of SCU on three selected paddy soils and (iii) To determine the effect of SCU on rice yield in the field. Laboratory experiments were conducted to evaluate physical and chemical properties of the SCU’s fertilizers. Urea (control), wax sulfur coated urea and polymer coated sulfur coated urea were determined for total N and S content, coating thickness and percentage of coating. Laboratory studies were also conducted to determine the effect of SCU on urea transformation, ammonia volatilization and pH change in three selected rice soils; Chempaka Series (Typic Paleudult), Lubok Itek Series (Typic Fluvaquent) and Tok Yong Series (Typic Paleudult). Two types of SCU fertilizers were used (i) Polymer coated sulfur coated urea (PCSCU) and (ii) Wax sulfur coated urea (WSCU). Urea, urea + Sulfur (6%) and urea + sulfur (17%) fertilizer were used as control treatments. Data were determined every week during 12 weeks incubation. Rice variety MR220 was selected to evaluate the efficacy of selected SCU. This study was conducted at Kampung Mahligai, Kelantan (05°56.770 N 102°17.684 E). The experimental design used was Factorial Randomize Complete Block Design (RCBD). Different treatments consisting of selected SCU were applied. The treatments were T1: Urea 120 kg/ha at split application (control treatment), T2: PCSCU 60 kg/ha at basal application, T3: PCSCU 60 kg/ha at split application, T4: PCSCU 120 kg/ha at basal application, T5: PCSCU 120 kg/ha at split application T6: WSCU 60 kg/ha at basal application T7: WSCU 60 kg/ha at split application T8: WSCU 120 kg/ha at basal application T9: WSCU 120 kg/ha at split application, T10: Urea + sulfur (6%) without coating 120 kg/ha at split application and T11:Urea + sulfur (17%) without coating 120 kg/ha at split application. Soil samples were collected at day 14, day 28, day 44, day 64, day 78 and day 94 after planting for determination of plant height, pH in soil and ammonium content. At maturity, plant was determined for N and S stage (length and number of panicle and tiller). Soil also was determined for N and S concentration and nutrient uptake. The coating thickness and the percentage of coating of the WSCU were thicker than the PCSCU. The thickness of fertilizer coatings was in the range of 30.3 μm-49.3 μm depending on the coating type. WSCU showed higher value (49.3 μm) of coating among the fertilizers. PCSCU has a lower value (30.3 μm) of coating. Laboratory study showed that WSCU treatment had the lowest NH3volatilization loss among the treatments for the three selected soils. Ammonia volatilization losses became 20 to 35% less in three selected soils. The NH4 +-N released from the fertilizer was affected by the types of fertilizer where WSCU had the lowest NH4+-N release for three selected soils. When urea was applied to soil, hydrolysis occurs rapidly to form NH4 +-N in soil. The pH increased rapidly after the treatments applied to the soil for three selected soils in week one. The uncoated urea showed higher pH compared to coated urea treatments. Field study using Lubok Itek series and rice variety MR220 were conducted. Results showed significant differences (P≤0.05) on grain yield. The highest grain yield is 5.4 t/ha was recorded from treatment WSCU 120 kg/ha at split application (T9). Treatment PCSCU at 60 /ha with basal application showed the lowest grain yield (3.3 t/ha) among the treatments. The highest straw yield was 9.83 t/ha recorded from treatment PCSCU 120 kg/ha at split application and U+S 17% 120 kg/ha without coating at split application (T11) while treatment PCSCU 60kg/ha as basal application (T2) showed the lowest straw yield (7.67 t/ha). Furthermore, there were significant differences (P≤0.05) on pH and ammonium content in soil, plant height, 1000 grain weight, number of tiller, number panicles, panicles length, plant length, N uptakes (plant, grain and straw), S uptakes (plant, grain and straw), N and Scontent, nutrients N and S uptake, yield and parameter at harvest concentration in (grain and straw) and S concentration in soil. No significant different occurred in N concentration in soil. Under control condition tested on three selected paddy soils showed that coated urea rtilizer give the best results compared to uncoated urea fertilizer. Wax sulfur coated urea fertilizer showed the capability to reduced ammonia volatilization loss effectively compared to uncoated urea fertilizer. The different results were obtained when the field trial carried out. As a conclusion, uncoated urea fertilizer is an excellent fertilizer when applied to Lubok Itek Series soil (flooded soil) which gives similar result with sulfur coated urea fertilizer. Sulfur coated urea fertilizer did not increased rice yield as compared to control treatment. The use of sulfur coated urea fertilizer at half the recommended nitrogen rate did not produce higher rice yield. Uncoated urea fertilizer is more economical relatively compared to coated urea in terms of price which is cheaper and easily available in markets.